Effects of nitrogen fertilization on preference of Cotesia plutellae to Diamondback moth - Khairuddin, Muhamad Izzuddin (2015)
Diamondback moth (DBM), Plutella xylostella is a pest of cruciferous plants and has been labelled as the most destructive pest of crucifers in the tropics and subtropics. Cotesia plutellae has been found to be an effective parasitoid that helps to kill DBM. The tritrophic interaction between the host plant, insect pest and the parasitoid can be seen when nitrogen (N) supplied to the host plant are shown to gives effect on parasitoid preference to parasitize the insect pest. The objective of this study is to determine N fertilization rate that is most preferred by the C. plutellae to DBM. In this study, DBM were collected from a local commercialized mustard farm and reared in 3 different cages which contain mustard that was fertilized with different rates of N, which are 0, 140 and 280 kg N/ha. DBM larvae cultured on these plants were used for the parasitoid preference test. Female C. plutellae were used to determine its preference on DBM larvae that fed on different rates of N. The parameter recorded was the time taken by C. Plutellae to go the preferred treatment. The result indicates that C. plutella prefer to attack DBM that fed on plants that were treated with higher N concentrations. However, there is no significant effect were recorded when the experiment between the normal and high N concentration was conducted. Information obtained from this study can be used by farmers to determine the fertilization rate that can control DBM population by attracting C. plutellae to parasitize the DBM.